2015
DOI: 10.1007/s00425-015-2444-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N2-fixing plant growth promoting endophytic and epiphytic bacterial community of Indian cultivated and wild rice (Oryza spp.) genotypes

Abstract: The diversity of endophytic and epiphytic diazotrophs in different parts of rice plants has specificity to the niche (i.e. leaf, stem and root) of different genotypes and nutrient availability of the organ. Inoculation of the indigenous, polyvalent diazotrophs can facilitate and sustain production of non-leguminous crops like rice. Therefore, N2-fixing plant growth promoting bacteria (PGPB) were isolated from different parts of three Indian cultivated [Oryza sativa L. var. Sabita (semi deep/deep water)/Swarna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 37 publications
1
37
1
2
Order By: Relevance
“…In this case, QS was proved to regulate, by means of acyl-homoserine lactone (AHL) diffusible signal molecule (identified as N-3-oxooctanoyl-L-homoserine lactone (OOHL)), such life functions of bacteria as forming of cell aggregates, called symplasmata, and interrelations between bacterium and host, including the colonization of plant tissues and promotion of rice growth [9]. The potential beneficial effects of P. agglomerans on rice growth has been confirmed recently by Banik et al [135], who identified the presence of 2 Pantoea spp. strains among 11 diazotrophic bacterial isolates from rice plants in India, which possessed the nifH (nitrogen fixation) gene and promoted the growth of rice seedlings.…”
Section: Growth Promotion Of Cultivable Plantsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case, QS was proved to regulate, by means of acyl-homoserine lactone (AHL) diffusible signal molecule (identified as N-3-oxooctanoyl-L-homoserine lactone (OOHL)), such life functions of bacteria as forming of cell aggregates, called symplasmata, and interrelations between bacterium and host, including the colonization of plant tissues and promotion of rice growth [9]. The potential beneficial effects of P. agglomerans on rice growth has been confirmed recently by Banik et al [135], who identified the presence of 2 Pantoea spp. strains among 11 diazotrophic bacterial isolates from rice plants in India, which possessed the nifH (nitrogen fixation) gene and promoted the growth of rice seedlings.…”
Section: Growth Promotion Of Cultivable Plantsmentioning
confidence: 98%
“…strains among 11 diazotrophic bacterial isolates from rice plants in India, which possessed the nifH (nitrogen fixation) gene and promoted the growth of rice seedlings. All these findings are very significant because rice is the staple food of 50% of world's population and 80% the population of Asia [135].…”
Section: Growth Promotion Of Cultivable Plantsmentioning
confidence: 99%
“…Others Azospirillum spp. have been described to produce siderophores (Banik et al, 2016;Sahoo et al, 2014).…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
“…For this reason, this genus has been received an increased attention. Banik et al (2016) used new Azospirillum strains for improvement of rice production. Inoculation studies with Azospirillum spp.…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
“…This pathogen is controlled using benzimidazoleand phenylpyridylamine-based fungicides sprayed directly on the seed pieces in the planting groove (Tokeshi & Rago, 2005). However, synthetic products can be replaced by biocontrol agents (Banik et al, 2016;Raza et al, 2016). Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%